Pendampingan Penyusunan Business Plan bagi Pelaku Industri Kue Karasa di Kecamatan Cempa Kabupaten Pinrang: Assistance in the Preparation of a Business Plan for Karasa Cake Industry Players in Cempa District, Pinrang Regency - Darwis Darwis; Besse Faradiba; I Nyoman Budiono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Small Micro Enterprises (SMEs) significantly contribute to the national economy, especially home industries. However, many business people still need to have a written business plan. This training activity aims to increase the knowledge and skills of Karasa cake industry players in making business plans. The target of the activity is the Karasa cake industry players who are members of the Karasa industrial center in Cempa District, Pinrang Regency. The training is delivered using participatory methods such as lectures, interactive discussions, and assistance in preparing business plan proposals. The pre-test and post-test measured participants' understanding of the business plan. The results of the training achieved were that the output of this activity was to provide knowledge for home industry players to develop the Karasa cake business by entering a broader market, and the outcome of this activity was that the Karasa cake industry had skills in making business planning proposals.